VD_FINDINFO 10/2015 vom 27. März 2015 - VD Tribunal cantonal (2015)
RÉCUSATION, CONFLIT D'INTÉRÊTS, ADMISSION DE LA DEMANDE | 6 al. 1 let. a ROTC, 6 ROTC, 47 al. 1 let. f CPC (CH), 47 CPC (CH), 48 CPC (CH), 8a al. 3 CDPJ, 8a CDPJ, 8b al. 4 CDPJ